Barriers of Thrombolysis Therapy in Developing Countries - Ghandehari, Kavian (SAGE-Hindawi Access to Research, 2011)
The developing world carries the highest burden of stroke mortality and stroke-related disability. The number of stroke patients receiving r-tPA in the developing world is extremely low. Prehospital delay, financial constraints, and lack of infrastructure are main barriers of thrombolysis therapy in developing countries. Until a cheaper thrombolytic agent and the proper infrastructure for utilization of thrombolytic therapy is available, developing countries should focus on primary and secondary stroke prevention strategies. However, governments and health systems of developing countries should efforts exerb for promotion of their infrastructure of stroke care.